Shades of green growth scepticism among climate policy researchers. - King, Lewis C.; Savin, Ivan; Drews, Stefan (Springer Nature, 2023)
Despite strong promotion of green growth by policymakers and international institutions, there is mounting criticism concerning the compatibility of continued economic growth with sustainability goals. Our global survey of 789 climate policy researchers reveals widespread scepticism in high-income countries, supporting the notion that as national income rises, environmental goals prevail over economic growth. This finding underscores the importance of considering alternative post-growth perspectives, including agrowth and degrowth strategies, to cultivate a more comprehensive discourse on sustainable development strategies.
https://v2.sherpa.ac.uk/id/publication/35369?template=romeo
Keywords: Cambios climáticos - Investigación; Ciencia - Aspectos sociales; Green growth; Agrowth; Degrowth; Scientific opinion